Aktivitas Panen dan Pascapanen Padi di Desa Rias Toboali Kabupaten Bangka Selatan: Rice Harvest and Post-Harvest Activities in Rias Toboali Village, South Bangka Selatan - Maryam; Evahelda; Puji Rufti Astuti; Patma Sari (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2025)
Rice harvest and post-harvest activities include several processes starting from selecting rice seeds/varieties, harvest age, harvest methods, collection, transportation, threshing, drying, milling and storage. The aim of this research is to determine the harvest and post-harvest process of rice in Rias Village, Toboali District, South Bangka Regency. Data collection was carried out through surveys using interviews and face to face with the help of questionnaires. Location selection was carried out by purposive sampling at rice planting centers. A total of 30 respondents were farmers and rice mill entrepreneurs who were selected randomly. The majority of respondents are in the productive age range (34-60 years), who are considered to have physical potential and dynamics that support business activities. In the harvest and post-harvest processes, the use of traditional harvesting tools such as ani-ani and sickles is still quite high, however, a combination with the use of modern technology such as combine harvesters is also used. The majority of respondents dry rice using tarpaulin, paying attention to weather conditions to determine the drying duration. The grinding machine used is the RMU (Rice Milling Unit) type which influences the grinding process, although some respondents still use traditional tools such as a pestle or mortar. The percentage of use of harvest and post-harvest tools, namely 48.5% of rice farmers in Rias Village already use modern harvest and post-harvest tools, and 51.5% still use traditional harvest and post-harvest tools.